2014
DOI: 10.1002/fuce.201400036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low‐Cost Separators for Increased Power Generation in Single Chamber Microbial Fuel Cells with Membrane Electrode Assembly

Abstract: We compared novel size-selective separators, namely the textile fabrics of polyphenylene sulfide (PPS) and sulfonated polyphenylene sulfide (S-PPS), and the nonwoven fabrics of polypropylene80 (PP 80) and PP 100, with commonly used ion exchange separators (Nafion 117 and cation exchange membane-7000; CMI-7000) in terms of power generation, oxygen diffusion, and biofilm formation in a single chamber microbial fuel cell. Size-selective separators exhibited more power generation than ion selective separators. MFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…[116] Although they showed that PEC performance can be engineered by controlling functional groups on ligand molecules, the use of Nafion is impractical for large scale applications due to its high cost. [117][118][119][120][121] For the immobilization on hydrophobic photoelectrodes or electrodes, hydrophobic polyaromatic functional groups can also be utilized as a surface anchoring group. [122][123][124] However, one can easily expect that this approach would have limited applications, as most artificial photosynthetic reactions are performed in aqueous solutions and that hydrophobic interactions are vulnerable to aggregation or disassembly.…”
Section: Functionalization Of Molecular Electrocatalystsmentioning
confidence: 99%
“…[116] Although they showed that PEC performance can be engineered by controlling functional groups on ligand molecules, the use of Nafion is impractical for large scale applications due to its high cost. [117][118][119][120][121] For the immobilization on hydrophobic photoelectrodes or electrodes, hydrophobic polyaromatic functional groups can also be utilized as a surface anchoring group. [122][123][124] However, one can easily expect that this approach would have limited applications, as most artificial photosynthetic reactions are performed in aqueous solutions and that hydrophobic interactions are vulnerable to aggregation or disassembly.…”
Section: Functionalization Of Molecular Electrocatalystsmentioning
confidence: 99%
“…The specific proton conductivity (S H , S/cm) was determined using ohmic resistance (R oh ,Ω), thickness of the membrane (L m , μm), and working surface area (A, cm 2 ) in the following equation [13,19] Eq. (3)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In their study, 10-mm electrode spacing exhibited a power density of 284 mW/m 2 , whereas a 30-mm electrode spacing revealed a maximum power density of 229 mW/m 2 . The lower power density for the MFC equipped with a 0 mm spacing (93 mw/m 2 )might be due to a substantial increase in pH at the cathode electrode or due to higher oxygen diffusion from the cathode to the anode due to limited electrogenic activity [19]. Proper interspatial distances (3 and 6 mm) will be helpful for obtaining neutral pH on an air cathode by allowing higher proton transport from the anode to cathode and more OH -diffusion from the cathode to anode [21].…”
Section: Maximum Power Density Obtained In Mfcs With Variation In Elementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that the next generation of sustainable energy could come from microorganisms, particularly from anaerobic digestion, and microbial fuel cells (MFCs) are gaining acceptance as an alternative “green” energy technology . Meanwhile, marine sediments microbial fuel cells (MSMFCs) have been used as a renewable power source to remote environmental monitoring , .…”
Section: Introductionmentioning
confidence: 99%